Insight into the Functional Dynamics and Challenges of Exosomes in Pharmaceutical Innovation and Precision Medicine - Anu Sharma; Anita Yadav; Aparajita Nandy; Subhadip Ghatak (MDPI AG, 2024)
Of all the numerous nanosized extracellular vesicles released by a cell, the endosomal-originated exosomes are increasingly recognized as potential therapeutics, owing to their inherent stability, low immunogenicity, and targeted delivery capabilities. This review critically evaluates the transformative potential of exosome-based modalities across pharmaceutical and precision medicine landscapes. Because of their precise targeted biomolecular cargo delivery, exosomes are posited as ideal candidates in drug delivery, enhancing regenerative medicine strategies, and advancing diagnostic technologies. Despite the significant market growth projections of exosome therapy, its utilization is encumbered by substantial scientific and regulatory challenges. These include the lack of universally accepted protocols for exosome isolation and the complexities associated with navigating the regulatory environment, particularly the guidelines set forth by the U.S. Food and Drug Administration (FDA). This review presents a comprehensive overview of current research trajectories aimed at addressing these impediments and discusses prospective advancements that could substantiate the clinical translation of exosomal therapies. By providing a comprehensive analysis of both the capabilities and hurdles inherent to exosome therapeutic applications, this article aims to inform and direct future research paradigms, thereby fostering the integration of exosomal systems into mainstream clinical practice.